Training Load, Aerobic Capacity and Their Relationship With Wellness Status in Recreational Trail Runners - Matos, Sérgio; Clemente, Filipe Manuel; Brandão, António; Pereira, Joel; Rosemann, Thomas; Nikolaidis, Pantelis Theodoros; Knechtle, Beat (Frontiers in Physiology, 2019)
The present study aimed to analyze the relationship between variables related to the internal and external loads of training and competition races as well as to athletes’ perceptions of well-being measured throughout the course of a four-week mesocycle. It was also aimed to analyze the intra- and inter-week variations in terms of training load and well-being. The study included the participation of 47 men recreational athletes competing in the national championships of trail running in Portugal (age: 34.85±8.88 years; height: 1.77±0.58 m; body mass: 65.89±3.17 kg). During the four weeks, subjective perception of effort (RPE), training time (min), session-RPE (sRPE), distance covered (km) and perception of well-being (Hooper's questionnaire) were monitored. Weekly RPE was greater in week 1 than in week 3 (p = 0.001; d = 0.563, small effect). Moreover, weekly sRPE was greater in week 1 than in week 2 (p = 0.001; d = 0.441, small effect). The correlations between the well-being variables and RPE that were found to be significant with small magnitudes are those between sleep and RPE (r = 0.287; p = 0.001), stress and RPE (r = 0.217; p = 0.001), fatigue and RPE (r = 0.191; p = 0.001), muscle soreness and RPE (r = 0.240; p = 0.001), and Hooper’s index and RPE (r = 0.279; p = 0.001). Among the variables of the Cooper test and the competition race load, it was verified that VO2max had a negative correlation of an average magnitude with pace (r = -0.396, p = 0.015). The findings of the study suggest that small variations in training stimulus during the period of analysis and that increases in maximal oxygen uptake result in improvements in the performance of trail running athletes when considering the running speed in the race.